UJI AKTIVITAS ANTIOKSIDAN INFUSA SEMANGGI (Marsilea crenata C. Presl) MENGGUNAKAN METODE DPPH (1,1-Diphenyl-2-PicrylHydrazyl) - Tiara Juliar Subakti; IAK Pramushinta; AS Sinulingga; SA Devi (LPPM Universitas Abdurrab, 2024)
Changes in lifestyle and environment now increase the risk of exposure to free radicals that cause degenerative diseases. Compounds needed to neutralize free radicals are antioxidants. One source of antioxidants is clover (Marsilea crenata C. Presl), which has previously been studied and has shown no antioxidant activity in various extraction solvents, but the clover infusion method with water solvent has not been studied, so the purpose of this study was to determine the antioxidant activity of clover infusion (Marsilea crenata C. Presl). This research method uses the DPPH method, then the antioxidant activity test of clover infusion (10% b/v) with a concentration of 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, and vitamin C as a positive control measured by a UV-Vis spectrophotometer. The absorbance value obtained at the maximum DPPH wavelength (516 nm) was used to calculate the linear regression equation of concentration and% inhibition. The results of the study obtained the IC50 value of clover infusion of 804.0 ppm and vitamin C as a positive control of 29.1 ppm. The conclusion of the study is that clover infusion shows no antioxidant activity (IC50 > 500 ppm), while vitamin C shows very strong antioxidant activity (IC50 > 50 ppm). Further research suggestions are related to the development of clover plant extraction methods and solvents (Marsilea crenata C. Presl) and antioxidant activity test methods.